Financial accounting : - Alexander, David (Financial Times, 2001)
Aimed at undergraduate/ MBA students worldwide taking a first course in financial accounting.Traditionally, local language texts have been used to teach this first course in financial accounting, as English language texts from the UK and US tend to focus exclusively on their respective standards and are generally too low level in their approach or place too much emphasis on bookkeeping. Over the past few years, the way in which this course has been taught has changed dramatically due to an increase in degree programmes being taught in the English language; a growing need for students to learn English accounting terms and expressions and increased dominance of International Accounting Standards in accounting practice throughout the world. Reflecting these changes this new text provides a complete introduction to financial accounting written in the accounting rules of the International Accounting Standards Committee (IASC).